Exploring factors that influence restorative experience, place attachment and customer voluntary performance among backpackers in their Malaysian enclaves / Thinaranjeney Thirumoorthi - Thinaranjeney, Thirumoorthi (2015)
Backpacker enclaves are a crucial part of backpacking experience. The enclaves are restorative spaces which reduce stress of travelling among backpackers from previous destination, unfamiliar culture and language. Despite this, little information is available on the restorative potential of the enclaves. This study conceptualises the importance of restorative qualities of the backpacker enclaves. Using a mixed method, the study seeks to examine the relationship between restorative experience, place attachment and customer voluntary performance (CVP). Attention Restoration Theory (ART) and Place Attachment Theory (PAT) were used to explain the phenomenon. Four scales were developed (physical environment, social support, restorative experience and place attachment) using rigorous scale development procedures. A total of 30 backpackers were in-depth interviewed, followed by quantitative self-administered questionnaire on 840 backpackers from eight most frequented backpackers’ enclaves in Malaysia. Structural equation modelling (SEM) was used to validate the hypothesized model. This study verifies the applicability of ART that the enclaves enable backpackers to recover from travel fatigue that often results from direct attention, concurrently, to many new stimuli. Physical environment, social support and personality are found to influence restorative experience of backpackers which subsequently affect place attachment and customer voluntary performance. Furthermore, the roles of restorative experience and place attachment as a mediator are established. The findings also support sources of social support as a moderator between social support and restorative experience. iv The theoretical research contribution lies in the scale development, extension and verification of ART, PAT, CVP and personality in backpacking tourism. Methodologically, this study contributes to the development of four context-based instruments. Findings on the restorative elements- Safety, Coherence, Quietness, Fascination, Novelty and Escape must be emphasized in the promotion and marketing as a selling point of the destination. The destination managers must give importance to these attributes in regenerating the existing and development of new enclaves. This study gives substance to the advancement of theoretical knowledge and development of the backpacker enclaves.